Patient-Reported Outcome Measures (Pain, Function, and Quality of Life) After Aseptic Revision Total Knee Arthroplasty. (21st October 2020) - Piuzzi, Nicolas S.; Siddiqi, Ahmed; Warren, Jared; Anis, Hiba K; Bloomfield, Michael R; Briskin, Isaac; Brooks, Peter J; Higuera-Rueda, Carlos A; Kamath, Atul F; Klika, Alison; Krebs, Olivia; Krebs, Viktor E; et al.
Update: This article was updated on October 26, 2020, because of a previous error. On page e114(1), in the byline, the listed authors that had read "Nicolas S. Piuzzi, MD, and Cleveland Clinic OME Arthroplasty Group*" now reads "Ahmed Siddiqi, MD, MBA, Carlos A. Higuera-Rueda, MD, Viktor E. Krebs, MD, Robert M. Molloy, MD, Alison Klika, MS, Nicolas S. Piuzzi, MD, and the Cleveland Clinic OME Arthroplasty Group*." Background: Despite the growing frequency of revision total knee arthroplasty (rTKA), there is limited information regarding patient-reported outcome measures (PROMs) after that procedure. Therefore, the purpose of this study was to determine (1) PROM improvements in pain, function, quality of life (QOL), and global health and (2) predictors of PROMs for patients undergoing aseptic rTKA as determined using a multilevel model with patients nested within surgeons. Methods: A prospective cohort of 246 patients who underwent aseptic rTKA from January 2016 to December 2017 and had baseline and 1-year postoperative PROMs were analyzed. The most common surgical indications were aseptic loosening (n = 109), instability (n = 73), and implant failure (n = 64). The PROMs included in this study were the Knee injury and Osteoarthritis Outcome Score (KOOS)-Pain, -Physical Function Short Form (PS), and -Quality of Life (QOL) as well as the Veterans Rand-12 (VR-12) Physical Component Summary (PCS) and Mental Component Summary (MCS). Multivariable linear regression models with patients nested within surgeons were constructed for predicting change in PROMs from baseline to 1 year. Results: The mean 1-year postoperative improvements in the KOOS-Pain and PS PROMs were 30.3 and 19.15 points, respectively, for the overall rTKA series. Improvement in the KOOS-Pain was associated with older age, baseline arthrofibrosis, lower baseline pain, and non-Medicare/Medicaid insurance and worsening of the scores was associated with multiple prior surgical procedures and instability. Improvement in the KOOS-PS was associated with baseline arthrofibrosis and female sex and worsening was associated with limited baseline function, an instability diagnosis, multiple prior surgical procedures, and increased hospital length of stay (LOS). Overall, the mean KOOS-QOL improved by 29.7 points. Although the mean VR-12 PCS improved, 54.9% of the patients saw no clinical improvement. Additionally, only 31.3% of the patients reported improvements in the VR-12 MCS. A multilevel mixed-effects model with patients/operations nested within surgeons demonstrated that the differences in the surgeons' results were minimal and explained only ∼1.86%, ∼1.12%, and ∼1.65% of the KOOS-Pain, KOOS-PS, and KOOS-QOL variance that was not explained by other predictors, respectively. Conclusions: Overall, patients undergoing aseptic rTKA had improvements in pain, function, and QOL PROMs at 1 year. Although overall QOL improved, other global-health PROMs remained unchanged. The associations highlighted in this study can help guide the preoperative clinical decision-making process by setting expectations before aseptic rTKA. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.